Developing gender principles for dealing with the legacy of the past - Ahmed, Yasmine (International journal of transitional justice, 2016)
This Note documents the motivations, process and challenges in developing the 10 Gender Principles for Dealing with the Legacy of the Past in Northern Ireland. The Principles are the outcome of a targeted intervention by a group of women from civil society and academia in Ireland and the UK to challenge the exclusions of ongoing negotiations to agree on a process to deal with the past. The Principles were shaped by a small-scale consultation with women bereaved by the conflict. The Note discusses some of the implications of the initiative for efforts elsewhere to craft practical feminist interventions into transitional justice processes, including the challenges inherent to such work.